PENGARUH PERTUMBUHAN PDRB DAN IPM TERHADAP KEMISKINAN KABUPATEN SAMPANG JAWA TIMUR - Nasrulloh, Rangga Ivan (Jurnal Ekonomika : INDEPENDEN, 2025)
This study aims to analyze the significant and insignificant effects of Gross Regional Domestic Product (GRDP) and Human Development Index (HDI) on poverty in Sampang Regency. The data used is GRDP data for the period 2004-2022. The research method used to analyze is the Multiple Linear Regression Test method, this method is used to process data using the E-views 13 application which can see the effect of GRDP and HDI on poverty. Based on the results of the research analysis, Sampang Regency in 2004-2022 the effect of GRDP on poverty was negatively insignificant, the effect of HDI on poverty was negatively significant and the effect of GRDP and HDI on poverty was negatively significant.